The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.5539/mas.v2n4p3
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Setting Times of Low Calcium Fly Ash-based Geopolymer Mortar

Abstract: Geopolymer is a novel binding material produced from the reaction of fly ash with an alkaline solution. In Geopolymer mortar, Portland cement is not utilized at all. In this research, the influence of various parameters on the short term engineering properties of fresh and hardened low-calcium fly ash-based Geopolymer mortar were studied. Tests were carried out on 50 x 50 x 50mm cube Geopolymer mortar specimens. The test results revealed that as the concentration of alkaline activator increases, the compressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(107 citation statements)
references
References 10 publications
4
74
0
2
Order By: Relevance
“…It also has been shown to affect the workability of a mixture for both low calcium [43] and high calcium [17] fly ash based geopolymer concretes. This trend of water content affecting on the workability and later on compressive strength is the same with the conventional Portland cement concrete, where the chemical reaction involved is hydration process [44]. Furthermore, from the review of some previous studies, it seems that variation in chemical composition of the fly ash has less effect on the workability, with the exclusion of flash setting problems.…”
Section: Fresh State Behaviorsmentioning
confidence: 66%
See 1 more Smart Citation
“…It also has been shown to affect the workability of a mixture for both low calcium [43] and high calcium [17] fly ash based geopolymer concretes. This trend of water content affecting on the workability and later on compressive strength is the same with the conventional Portland cement concrete, where the chemical reaction involved is hydration process [44]. Furthermore, from the review of some previous studies, it seems that variation in chemical composition of the fly ash has less effect on the workability, with the exclusion of flash setting problems.…”
Section: Fresh State Behaviorsmentioning
confidence: 66%
“…Some researches which utilize low calcium fly ash [44,46] indicates that the reaction of geopolymerization would not start without elevated temperature curing and did not harden for at least one day. On the other side, a work conducted by Somna et al [47] shows that curing in the room temperature is possible when utilizing the high calcium fly ash with a high concentration of alkaline activator.…”
Section: Fresh State Behaviorsmentioning
confidence: 99%
“…It has been found that the compressive strength is proportional to the concentration of NaOH solution and reaches the maximum value 25.48 MPa at 12 M (Figure 8). The literature [26,27] showed that the increase in the concentration of hydroxyl ions leads to the following reaction processes: (1) the liberation of Si and Al ion species from aluminosilicate raw materials; (2) the formation of stronger ion pairs; and (3) the acceleration of polycondensation rates. These processes all contribute to the development of geopolymer strength.…”
Section: Effect Of Naoh Concentrationmentioning
confidence: 99%
“…Low CaO content in ash lengthens setting time [6,7] states that low-calcium ash-based geopolymers ordinarily have a setting time of nearby 2 hours. Previous study [8] revealed factors affecting setting time of matrices are morphology, reactivity and Ca content of ash.…”
Section: Introductionmentioning
confidence: 99%